Modeling the Effect of Family Atmosphere, School Atmosphere, and Social Support on Aggressiveness and Addiction Preparedness Among Students: The Mediating Role of Extroversion - Zohre Shahriari Shaghaghi; Afsaneh Ghanbaripanah; Parisa Tajalli (Gonabad University of Medical Sciences, 2020)
Background: The increased rates of aggression and drug abuse among students are considered an important health issue. Therefore, the present study aimed to investigate the relationship between the emotional atmosphere of the family, the school climate, perceived social support, aggressive behavior, and preparedness for addiction among students, considering the mediating role of extroversion. Methods: This research used the analytical-correlative method. Also, the statistical population included all high school students in Tehran, during the academic year of 2017-2018.  Results: The school environment had a significant direct effect on the preparedness for addiction. Besides, we identified the indirect effect of the school environment on irregular drug addiction. The hypothesized model showed the full effect and the nonsignificant direct effect of perceived social support on aggressive behavior. Moreover, there was a significant indirect effect between perceived social support and aggressive behavior. However, there was no direct or indirect effect between perceived social support and preparedness for addiction and the existence of extroversion's mediating function.  Conclusion: Thus, teachers and school administrators are recommended to discuss the psychological environment of the family, the school atmosphere, and perceived social support.